Method development for the determination of 1, 1-dimethylhydrazine by the high-performance liquid chromatography–mass spectrometry technique. Issue 4 (August 2018) - Susinskis, Igors; Mekss, Peteris; Hmelnickis, Juris
Unsymmetrical dimethyl hydrazine is highly toxic, carcinogenic compound, widely used for organic synthesis and drug development. Therefore, due to its high reactivity, direct analysis is problematic. Current study proposes to use derivatization reaction to increase selectivity and sensitivity of high-performance liquid chromatography–mass spectrometry method. Different derivatization agents were tested and optimal reaction media was found. Derivatization was performed by using small amounts of reagents to lower the cost of analysis. The full validation of the method was performed and it can be used in a routine control in pharmaceutical analysis. Method sensitivity is 0.15 ppm, and linearity range is 0.15–2.70 ppm.